Основні принципи діяльності Конституційного Суду України: структурний вимір - Кампо, В.М. (Альманах права, 2012)
У статті на основі аналізу положень Конституції України, Закону України «Про Конституційний Суд України», Регламенту Конституційного Суду України, а також правових позицій єдиного органу конституційної юрисдикції в Україні досліджується структура принципів діяльності Конституційного Суду України. В статье на основе анализа положений Конституции Украины, Закона Украины «О Конституционном Суде Украины», Регламента Конституционного Суда Украины, а также правовых позиций единого органа конституционной юрисдикции в Украине исследуется структура принципов деятельности Конституционного Суда Украины. The article concerns the structure of principles of activities of the Constitutional Court of Ukraine on the grounds of analysis of provisions of the Constitution of Ukraine, the Law of Ukraine «On the Constitutional Court of Ukraine», the Rules and Procedures of the Constitutional Court of Ukraine as well as legal positions of the sole body of the constitutional jurisdiction of Ukraine. In particular, it has been analyzed the principle of the rule of law and researched its components: justice, commensurability (proportionality), legal certainty. It has been structured the principle of independence of judges of the Constitutional Court of Ukraine. The article also analyses principles of collectivity, equality of judges, publicity, fullness and depth of consideration of cases and validity of decisions adopted by the Constitutional Court of Ukraine. As a result, the principles of activities of the Constitutional Court of Ukraine are determined as the structurally ordered system of interconnected, interdependent legal ideas, which in its totality achieve the goal of the Сonstitutional Сourt of Ukraine and determine its legal status.